Development of Amine Capillary Column Applied to the Analysis of Basic Compounds by Electrochromatography - Flor, Sabrina Andrea (2015)
An amine capillary column was developed in a fused-silica capillary as stationary phase and appliedto separation of basic compounds by capillary electrochromatography (CEC). The functionalizedcapillary was prepared by inmobilization of 3-Aminopropyl)triethoxysilane (APTES). TheCEC conditions including APTES and buffer concentration, pH and applied voltage were investigatedto obtain the optimal CEC system for the separation of three anesthetics as basic test molecules.The capillary column provided an efficiency of up to 20,000 plates/m. Lidocaine, ketamineand xilacine were baseline separated under the running conditions with 10 mM Na2HPO4 pH 9.0 asBGE. The applied voltage was 5 kV temperature was set at 25˚C and UV detection was performed.The resolutions were 4.97 and 1.53 for ketamine, lidocaine and xilacine, respectively. The columnused in CEC mode showed better separation of the anesthetics compared with those used in thecapillary zone mode. The comparison with reversed stationary phases used in HPLC in terms ofresolution (Rs), sensitivity (LOD), efficiency (N), precision (RSD), asymmetry (T) was also performed.This study provided an alternative way for the CEC separation of basic compounds anddemonstrated the improvement in the chromatographic parameters